Uji Kemampuan Bonggol Pisang Sebagai Nutrisi Mikroorganisme Dalam Mendegradasi Sampah Rumah Tangga Menjadi Kompos - Ain Khaer; Gyta Jeans; Budirman Budirman; Erwinda Alwi Rachman (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Waste is waste resulting from activities from households, offices and others. The amount of waste generated nationally is 175,000 tons per day or the equivalent of 64 million tons per year if using environmental assumptions, which can cause various problems including: beauty and comfort as well as human health problems, both within the individual, family and community scope.This research aims to determine the ability of local microorganisms from banana weevils in the household waste composting process to speed up decomposition. The type of research used in this research is a field experiment by carrying out treatment tests three times. The results of the research showed that compost with the addition of 150 ml MOL banana weevils took 20 days for composting, whereas for compost with the addition of 100 ml MOL banana weevils the composting time took 21 days and for compost with the addition of 50 ml MOL banana weevils for 21 days. The length of composting time is greatly influenced by the microorganisms present in the MOL added to the compost. Based on SNI 7030- 2004, the size of the material used for compost maturity requirements such as the C/N ratio has a value of (10-20):1. The conclusion of this research is that banana weevil MOL is able to degrade waste into compost according to SNI standards. From the three tests that have been carried out, the most effective result is the addition of 150ml of banana weevil MOL. It is better for people to use banana weevils as compost and for agricultural purposes because they can degrade waste.